Relationship between Organizational Culture and Creative Learning of Students at Alternative Secondary Schools in Bangkok Metropolis - จำปาฤทธิ์ ลลิตา; ประจงจิตร สนั่น; นิยมาภา อัจฉรา (Journal of Educational Review Faculty of Education in MCU, 2019)
The purposes of this research were to study: 1) levels of organizational culture of alternative schools in Bangkok Metropolis, 2) levels of creative learning of these students, and 3) relationship between organizational culture and creative learning of the students. A sample of 88 teachers from these secondary alternative schools was selected by a proportional stratified random sampling. The instrument for data collection was a questionnaire constructed by the researcher. The statistics used for data analyses were percentage, means, standard deviation, level, and Person’s product moment correlation coefficient. The research results were as follows: 1) Organizational culture of all aspects was rated at the high level; from which the aspect of beliefs had the highest means, followed by that of organizational culture of values. 2) All aspect of student creative learning was also rated at the high level; from which the aspect of child–centered creative learning was ranked at the top, followed by that of life-long creative learning. 3) The relationship between organizational culture and creative learning of these students was at the highest level with the statistically significant level of 0.01.